PENGARUH GREEN MARKETING DAN KESADARAN LINGKUNGAN TERHADAP PERCEIVED VALUE PRODUK ECO BAG MELALUI SIKAP PEDULI LINGKUNGAN SEBAGAI VARIABEL MEDIASI (Studi Kasus Pembelian Eco bag pada Konsumen Gen Z di Indomaret Kota Surabaya Barat Benowo) - Dwi Lailatul Zumroh; Dana Aditya (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The increasing environmental problems due to the use of single-use plastics encourages retail companies to implement environmentally friendly marketing strategies, one of which is through the provision of eco-bag products. This study aims to analyze the influence of green marketing and environmental awareness on the perceived value of eco-bag products with environmental awareness as a mediating variable. The object of the study was Generation Z consumers who purchased eco-bags at Indomaret in the West Surabaya Benowo area. This study used a quantitative approach with a survey method by distributing questionnaires to respondents selected using a purposive sampling technique. The data obtained were analyzed using descriptive analysis, measurement models, validity tests, structural models, path analysis tests, and T-tests. The results showed that green marketing and environmental awareness had a positive and significant effect on the perceived value of eco-bag products. In addition, green marketing and environmental awareness also had a positive effect on environmental awareness. Environmental awareness was proven to have a positive effect on perceived value and was able to mediate the influence of green marketing and environmental awareness on the perceived value of eco-bag products. These findings indicate that the formation of environmental awareness is an important factor in increasing the perceived value of environmentally friendly products. This study is expected to be a reference for retailers in designing more effective and sustainable green marketing strategies.